The Effect of Work Skills and Work Flexibility on Work Productivity trough Job Satisfaction of Gojek Partners in the City of Malang - Ni Kadek Dewi Iriani Putri; Harianto Respati; Mokhammad Natsir (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze how work skills and work flexibility affect work productivity through job satisfaction as an intervention variable among Gojek partners in the Malang City area. This study uses a quantitative methodology with a causality design. Using simple random sampling, questionnaires were sent to 120 selected Gojek partners to obtain initial data. A Structural Equation Modeling (SEM) based on linear regression analysis was used to analyze the data. This was done using the SPSS program. The results of the study indicate that work skills and work flexibility positively and significantly affect the productivity of Gojek partners. In addition, job skills and work flexibility also have a positive and significant effect on job satisfaction. Job satisfaction is also proven to have a positive and significant effect on work productivity, and also functions as a mediating variable in the relationship between job skills and work flexibility and work productivity. The results show that job satisfaction can increase with job skills and a more flexible work environment. Ultimately, this will have an impact on increasing the productivity of Gojek partners. It is hoped that this research will help digital platform managers create more flexible and sustainable HR management strategies.